Models of Care for Postacute COVID-19 Clinics: Experiences and a Practical Framework for Outpatient Physiatry Settings. (December 2021) - Verduzco-Gutierrez, Monica; Estores, Irene M.; Graf, Min Jeong P.; Barshikar, Surendra; Cabrera, Juan A.; Chang, Lynn E.; Eapen, Blessen C.; Bell, Kathleen R.
Abstract : Abstract: After surviving infection with the SARS-CoV-2 virus, individuals may have persistent symptoms and prolonged impairments that may last for weeks to months. The frequency and heterogeneity of persistent post-COVID conditions have created challenges in care. Specialty clinics are being established in response to an increasing need to care for patients with postacute sequelae of SARS-CoV-2 or long COVID syndrome. Although many post-COVID conditions can be bettered through a comprehensive rehabilitation plan, various clinical settings may benefit from differing models of coordinated care. We present five models of care in varying degrees of development and compare processes and adaptations to address the unique needs of each center and their unique patient populations. Forging a path to recovery will necessitate a multidisciplinary team with physiatry involvement to meet the distinctive needs of patients with postacute sequelae of SARS-CoV-2. Furthermore, it is imperative that there be equitable access to this care and commitment from healthcare institutions to provide resources for these programs. Abstract : Supplemental digital content is available in the text.